2015
DOI: 10.1007/s10147-015-0784-9
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of Goshajinkigan on peripheral neurotoxicity of FOLFOX therapy (GENIUS trial): a placebo-controlled, double-blind, randomized phase III study

Abstract: Goshajinkigan did not prevent oxaliplatin-associated peripheral neuropathy in this clinical trial. The clinical study was therefore terminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 29 publications
3
89
0
4
Order By: Relevance
“…A549, SKOV3) to paclitaxel. However, we did not observe neuroprotection of oxaliplatin with GJG consistent with lack of clinical evidence from a randomized phase III study of GJG combined with oxaliplatin [Oki, et al 2015]. …”
Section: Discussionsupporting
confidence: 76%
“…A549, SKOV3) to paclitaxel. However, we did not observe neuroprotection of oxaliplatin with GJG consistent with lack of clinical evidence from a randomized phase III study of GJG combined with oxaliplatin [Oki, et al 2015]. …”
Section: Discussionsupporting
confidence: 76%
“…About the safety of GJG, a recent phase 2, randomized, double-blind, placebo-controlled study concluded that GJG offers an acceptable safety margin and a promising effect in delaying the onset of grade 2 or greater oxaliplatin-induced peripheral neurotoxicity without impairing chemotherapy efficacy [48], confirming previous animal models findings [56]. To date, there are no strong recommendations about the use of specific neuroprotective agents and also the effectiveness of herbal medicines, such as GJG must be better elucidated [57][58][59]. Nevertheless, standard approaches, including amifostine and antidepressants have had limited efficacy and may themselves induce adverse side-effects, while herbal medicines has shown a better efficacy and safety profile.…”
mentioning
confidence: 65%
“…The majority of the articles reviewed reported results of randomized trials ( N = 11) [1921, 23, 24, 2628, 3133]. Other research designs included nonrandomized trials ( N = 5) [22, 3437], cross-sectional studies ( N = 2) [3, 11], cohort studies ( N = 2) [25, 29], case series ( N = 1) [38], and a crossover trial ( N = 1) [30].…”
Section: Resultsmentioning
confidence: 99%